An assessment on the technical and economic feasibility of mechanized rice straw collection in the Philippines - Balingbing, Carlito; Van Hung, Nguyen; Roxas, Ampy Paulo; Aquino, Daniel; Barbacias, Mary Grace; Gummert, Martin (MDPI, 2020)
The increasing utilization of rice combine harvesters in the Philippines has made collection of scattered rice straw difficult and laborious. While there are high demands for using rice straw, e.g., for feed or mushroom production, rice straw is predominantly burned in the field due to labor shortages and the high manual cost of collection, particularly for scattered rice straw harvested by combine harvesters. This study conducted an assessment and evaluated the feasibility of mechanized collection of rice straw by comparing the performance of two types of baler (i.e., roller and piston type) for two seasons—2019 wet and dry seasons at the International Rice Research Institute (IRRI) and in Nueva Ecija, the Philippines. The study collected data on fuel consumption, manpower requirements, and field capacity by operating the balers to collect scattered rice straw in the field and piled rice straw that was left in the field after threshing. The round baler operated at 35% lower effective field capacity (EFC) on piled rice straw than on scattered rice straw, while the square baler operated at 2.33 times and 5.79 times higher EFC compared with the round baler on piled and scattered rice straw, respectively. The square baler used for collecting scattered rice straw is more appropriate under Philippine conditions, with a significantly lower baling cost by about 68% and an average EFC that is 4.43 times higher compared to the round baler. With the increasing demand for rice straw as feedstock for ruminants and for other alternative uses, using mechanical balers to gather scattered rice straw in the field is a sustainable option for farmers to utilize the straw for value-adding purposes. This is a foremost study conducted in the Philippines to guide policy makers, development workers, and end-users on the suitability of either square balers or round balers to gather scattered rice straw in the field after rice harvesting with combines.